PHARMACOLOGICAL & PHYTOCHEMICAL EVALUATION OF YOGRAJ CHURNA: AN COMPOUND AYURVEDIC FORMULATION - Lekharu, *Sikha; Basumatary, Khagen (International Journal of Ayurveda and Pharma Research, 2016)
Yograj churna is an important Ayurvedic formulation containing Triphala (Amlakhi – Embelica officinalis, Bibhitaki – Terminalia bellerica, Haritaki – Terminalia chebula), Triakatu (Sunthi-Zingiber officinele, Maricha- Piper nigrum, Pippali – Piper longum), Vidanga (Embelia ribes Burm. f), Chitrakmula (Plumbago zeylanica Linn), Suddhashilajit (Asphaltum punjabianum), Swarnamakshika (Copper pyrite (CuFeS2), Raupyamakshika (Iron pyrite (Fe2S3), Lohabhasma (Iron Powder) and Mirsi (sugar) as main ingredient. of all the constituent were available and prepared accordingly as mentioned in Charak samhita, Chitsasthana, Panduroga adhyaya in Ayurvedic pharmacy, BHU. Though Yograj churna is very effective in anemia, it is useful in different disorder and as an excellent rejuvenator. But till date no work has been carried out to standardize the formulation. Hence the present study was undertaken to standardize the compound Ayurvedic formulation through Pharmacognostical and pharmaceutical evaluation. The sample was subjected for various Phytochemical parameters like water soluble extractive (11.39%w/w), alcohol soluble extractive (23.63% w/w), ash value (39.19% w/w), acid insoluble ash (36.38% w/w), loss on drying (8.86% w/w), the pH (5.03), TLC. The TLC, solvent system was methanol:ethyl acetate (by trial and error method), showed the presence of 4 spots Rf (0.1, 0.46. 0.76, 0.9). The phytochemical analysis showed the presence of Alkaloids, Glycosides, Saponins and Tanins. Thus the physiochemical and microscopic characters achieved may provide guidelines for standardization of formulation, Yograj churna.